2011
DOI: 10.4103/0971-6203.89970
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cutouts on output, mean energy and percentage depth dose of 12 and 14 MeV electrons

Abstract: Electron field-shaping cerrobend cutouts on the linear accelerator applicator have some effects on the output and percentage depth dose. These effects which arise from the lateral scatter nonequilibrium are particularly evident in higher energies and in cutouts with smaller radius. Dose measurements for circular, square, and triangular cutouts as well as open field was performed in a 10 × 10 cm applicator, using plane parallel type ion chamber with a 100 cm source surface distance. The Percentage Depth Doses c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Such applicators are expected to affect output factors (OFs), percentage depth dose curves (PDDs), and the shape of beam profiles. In particular, the lack of lateral scatter equilibrium occurring in small beam sizes (2) results in a shift towards the phantom surface of the depth of maximum dose in the PDD curves (3) . Additionally, a contribution from scattered and bremsstrahlung radiation generated by the collimator systems is expected (4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…Such applicators are expected to affect output factors (OFs), percentage depth dose curves (PDDs), and the shape of beam profiles. In particular, the lack of lateral scatter equilibrium occurring in small beam sizes (2) results in a shift towards the phantom surface of the depth of maximum dose in the PDD curves (3) . Additionally, a contribution from scattered and bremsstrahlung radiation generated by the collimator systems is expected (4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that the mixed beam has some advantages over electron or photon beams. For example, the electron beam is more sensitive to small fields [4] [5] than mixed or photon beams. Xiong et al conducted a research to optimize dose distribution of photon and electron combination in breast [6].…”
Section: Introductionmentioning
confidence: 99%
“…This capability leads to employ it in radiation therapy of nasal, breast, and parotid regions (1,2). On the other side, its usage is limited by the dependency of penumbra to the depth and influence of dose parameters of electron beam from the field size changing (3)(4)(5)(6)(7)(8). The issue of penumbra increment by depth is enhanced in some investigations by adding a narrow photon beam to the edge of the electron beam field (5) or mixing a low weight photon to electron beam field (4,9,10).…”
Section: Introductionmentioning
confidence: 99%